Modeling of Temperature Fields in Metals and Alloys under the Energy Impact of High-Pulse Power Ion Beams with Submillisecond Duration; Journal of Surface Investigation: X-ray, Synchrotron and Neutron Techniques; Vol. 19, iss. 4 - Ryabchikov A. I. Aleksandr Ilyich (2025, 2025)
The method of high-intensity implantation of high-power ion beams with submillisecond duration predetermines significant pulsed heating of the irradiated target’s surface layer with subsequent ultra-fast cooling. The numerical modeling was used to study dynamic variations in temperature fields in titanium (Grade 2), aluminum alloy (1013), Zr–1Nb alloy (E110), stainless steels (321 and 5140) differing significantly in physical and mechanical properties. The article has considered the temperature gradient dynamics in the near-surface layer and at great depths of matrix materials under the influence of submillisecond ion beams with a pulsed power density of up to 1 × 109 W/m2. The parameters of ion beams providing pulsed heating of the surface layer of various materials to the melting temperature have been determined. Both single-pulse and repetitively-pulsed irradiation were studied, including taking into account the heating of the material’s entire volume. It has been shown that after the end of the ion beam pulse, the high-speed heating of the surface layers of metals and alloys turns into ultra-fast cooling due to heat transfer into the main volume of the matrix material due to thermal conductivity